Pengaruh Biaya Operasional Berbanding Pendapatan Operasional (BOPO), Non Performing Loan (NPL), Loan To Deposit Ratio (LDR) Terhadap Kinerja Usaha (ROA) - ., Anysa; Rahardjo, Bambang (LPPM Institut Bisnis dan Informatika Kesatuan, 2017)
The study was based on a formulation of problems, namely are Operational Cost versus Operating Income (ROA), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) on Business Performance (ROA) at PT Bank Rakyat Indonesia (Persero) Tbk., PT Bank Negara Indonesia (Persero) Tbk., and Bank Mandiri (Persero) Tbk. The purpose of this research was to determine the effect of operational cost compared to Operating Income (ROA), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) on Business performance (ROA) at PT Bank Rakyat Indonesia (Persero) Tbk., PT Bank Negara Indonesia (Persero) Tbk, and Bank Mandiri (Persero) Tbk. The method used in this research is quantitative method. This method is used to predict the effect of one variable with another variable. In this study the variable X (Operating Expenses compared to Operating Income (ROA), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) are independent variables (free) and Y (Return On Asset) is the dependent variable (dependent). The data obtained was secondary, and to analyze the data, multiple regression analysis was used. During the observation period of the study showed that the data were normally distributed. Based on the test multicollinearity, heteroscedasticity test and autocorrelation test found no variable that deviates from the classical assumption tests, this shows that the available data are qualified to use a multiple linear regression model. Based on the results of the study it can be concluded that there is significant influence of operational costs when compared to Operating Income (ROA), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) PT Bank Rakyat Indonesia (Persero) Tbk., PT Bank Negara Indonesia (Persero ) Tbk, and Bank Mandiri (Persero) Tbk. with test results of multiple linear regression equation